Stable isotope fractionation in speleothems: laboratory experiments - Polag, Daniela; Scholz, Denis; Mühlinghaus, Christian; Spötl, Christoph; Schröder-Ritzrau, Andrea; Segl, Monika; Mangini, Augusto (Chemical geology, 2010)
In recent years, stalagmites have become important archives for paleoclimate. Several studies applying carbon and oxygen isotopes of stalagmites show a simultaneous increase of δ13C and δ18O along individual growth layers, which is interpreted as being indicative of isotope fractionation under disequilibrium conditions. In order to obtain robust paleoclimatic information from calcite precipitated under these non-equilibrium conditions it is important to improve the quantitative understanding of the corresponding isotope fractionation processes. Here we present laboratory experiments simulating calcite precipitation under cave-analogue conditions. The major focus was the investigation of the temporal evolution of the δ13C and δ18O values of the precipitated calcite for varying temperature, drip interval and initial SICaCO3. All experiments show an isotopic enrichment of both δ13C and δ18O with increasing distance from the point of drip water impinge. Longer drip intervals and higher temperatures result in a larger enrichment. In addition, the slope between δ18O and δ13C is lower for higher temperatures indicating faster oxygen isotope exchange between the water reservoir and the bicarbonate in the solution. In case of δ13C, the fractionation factor between the precipitated calcite and the bicarbonate in the solution, 13αCaCO3−HCO3−, shows a larger increase with higher temperatures in comparison to previous studies. This possibly indicates an increasing contribution of disequilibrium isotope fractionation processes for increasing temperatures, which are not accounted for by the equilibrium isotope fractionation factors. Furthermore, a quantitative determination of the calcite precipitation time, τp, and the oxygen isotope exchange time between the bicarbonate and the water, τb, yields faster reaction rates in comparison to previously published time constants, particularly at higher temperature (23°C).
Gesehen am 04.05.2023